Projecting the future of Ayapel Cienaga: A hydroecologic analysis under climate change scenarios (2020)
ABSTRACT : We developed a three-component model to evaluate the present and future hydrological behavior of Ayapel Cienaga under different scenarios of climate variability and human intervention associated with fishing and mining activities and the maintenance of levees. We calibrated the water balance with historical information on hydrological variables, water levels, stream discharges, fishing activities and gold mining records in the period 1985-2015. We use autoregressive statistical models to project climate scenarios that consider extreme variations in mean monthly rainfall, ENSO activity, temperature increases of 2°C, and levee breaks along the Cauca River. In addition, we incorporated two dynamic of systems models of bocachico fish population and mercury accumulation in the Cienaga. The simulations indicate that the Cienaga levels can be affected by extreme changes in rainfall associated with ENSO. The model estimates the fraction of water that could enter from the Cauca River due to levee breaks. Furthermore, using a fish dynamic population we could project the population and catch of bocachico. Finally, the mercury balance model due to mining in the region help to estimate mercury concentrations in water, fish and aquatic macrophytes matrices. This model offers a tool for management and decision-making in ecohydrological aspects of the Cienaga under different climate change scenarios.